Evaluation of Eight Serological Tests for Diagnosis of Imported Schistosomiasis - Kinkel, Hans-Friedemann (American Society for Microbiology, 2012)
The diagnosis of schistosomiasis in individuals from countries where the disease is not endemic is challenging, and few data are available on the accuracy of serological diagnosis in those patients. We evaluated the performance of eight serological assays, including four commercial kits, in the diagnosis of imported schistosomiasis in individuals from areas where the disease is not endemic, including six enzyme-linked immunosorbent assays using three different antigens, an indirect hemagglutination assay, and an indirect immunofluorescent-antibody test. To analyze the assays, we used a total of 141 serum samples, with 121 derived from patients with various parasitic infections (among which were 37 cases of schistosomiasis) and 20 taken from healthy volunteers. The sensitivity values for detection of schistosomiasis cases ranged from 41% to 78% and were higher for Schistosoma mansoni than for S. haematobium infections. Specificity values ranged from 76% to 100%; false-positive results were most frequent for samples from patients with cestode infections. By combining two or more tests, sensitivity improved markedly and specificity decreased only moderately. Serological tests are useful instruments for diagnosing imported schistosomiasis in countries where the disease is not endemic, but due to limitations in test sensitivities, we recommend the use of two or more assays in parallel.